Kepemimpinan Transformasional Terhadap Employee Performance Melalui Employee Empowerment Dan Employee Engagement Sebagai Variabel Intervening Pada PT. Bank Mandiri (Persero) Tbk Kota Medan - Wirandini, Tasya Ayu; Ritonga, Ilham Mubaraq; Tamba, Muller (Graha Mitra Edukasi, 2023)
This study aims to determine transformational leadership on employee performance through employee empowerment and employee engagement as interverning variables at PT. Bank Mandiri Medan City. The total population in this study was visiting 120 people, by using a saturated sample, the total sample of the number of employees of PT. Bank Mandiri Medan City. The analytical technique used is path analysis. While the type of research used in this study is a quantitative approach, the method used in this research is statistics with data collection techniques through questionnaires to all employees of PT. Bank Mandiri Medan City. The results showed that Transformational Leadership had a positive and significant effect on Employee Empowerment. Transformational Leadership has a positive and significant effect on Employee Engagement. Transformational Leadership has a positive and significant effect on Employee Performance. Employee Empowerment has a positive and significant effect on Employee Engagement. Employee Engagement has a positive and significant effect on Employee Empowerment at. Meanwhile, they jointly state that Transformational Leadership, Employee Empowerment, and Employee Engagement have a significant influence on Employee Performance.